Analisis Faktor Brand Awareness, Brand Exposure, Customer Engagement, Dan Electronic Word-of-Mouth Dalam Pemasaran Melalui Media Sosial Pada The Body Shop Indonesia - Lovely Pomalaa; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Based on a Top Brand Award survey conducted by Frontier Consulting Group, in 2017 The Body Shop Indonesia has experienced a decrease in brand awareness level compared to 2016. The degresssion of brand awareness level in The Body Shop Indonesia made the company must be able to increase brand awareness level to sell products quickly and obtain consumers easily. In marketing through social media, brand awareness factor is influenced by brand exposure, customer engagement, and electronic word-of-mouth. Instagram social media optimization allows The Body Shop Indonesia to get more attention from consumers. The sample used in this study as much as 80 respondents with sampling technique is incidental sampling. Data collection was obtained by distributing online questionnaires to respondents. Data processing is done by using descriptive statistical analysis and basic assumption test. The result of data category on brand awareness is high with a percentage of 73.34%, brand exposure is high with a percentage of 67.83%, customer engagement is less with a percentage of 56.74%, and electronic word-of-mouth is less with a percentage of 46.05%. Recommendations that can be given are by improving two variables in marketing through social media, namely customer engagement and electronic word-of-mouth.